First study of in vitro protective effect of Lepidium meyenii (Maca) on frozen–thawed bovine spermatozoa - Johanna Leiva-Revilla; Miriam Rolón; Abolghasem Siyadatpanah; Maria de Lourdes Pereira; Veeranoot Nissapatorn (Veterinary World, 2022)
Background and Aim: Lepidium meyenii Walp (Maca) is an herbaceous plant that grows in the Peruvian Andes and it has been widely used as a nutritional supplement and fertility enhancer and has been used in the treatment of a variety of diseases, such as rheumatism, respiratory disorders, and anemia. The most notable feature of Maca is its potent antioxidant capacity, which helps in the scavenging of free radicals and protection of cells from oxidative stress. This study aimed to evaluate the in vitro effect of Maca extract on thawed sperm cells from bulls.